Assessment of Free Dietary Glutamate Intake among Malays and Chinese in the Klang Valley, Malaysia - Mohsin, Khairunnisak (2009)
Dietary intake assessment is a qualitative or quantitative evaluation of the degree of intake likely to happen, in which the estimation is made by multiplying the food consumption by the chemical concentration in the respective foods. In the present study, assessment of free dietary glutamate has been carried out among 360 Malay and Chinese adults in the urban area of Klang Valley, Malaysia. The food consumption data was obtained through a survey using food frequency questionnaires (FFQ) and condiments usage forms. In addition to that, the free glutamate content of food and condiments were analysed by High Performance Liquid Chromatography (HPLC) utilizing pre-column derivatization and fluorescence detection. Subsequently, using both data from survey and sample analysis, the study estimated free dietary glutamate intake of the respondents involved in the study. Results from the survey revealed that the average total food consumption by total respondents was 843 g/person/day, with significant (p=0.017) higher consumption among the Chinese (948 g/person/day) compared to the Malays (793 g/person/day). The study also showed that consumption of condiments by both Malay and Chinese households was comparable, at 7.56 and 6.87 g/person/day, respectively. Chinese respondents, however, used more types of condiments compared to Malays. Meanwhile, results from sample analysis showed that the average free glutamate content in processed foods ranged from 0.34 ± 0.20 to 4.63 ± 0.41 mg/g. In food dishes, it was as low as 0.24 ± 0.15 mg/g in roti canai to 8.16 ± 1.99 mg/g in dim sum. Relatively, the free glutamate content was found to be higher in condiments at 0.28 ± 0 mg/g in mayonnaise to 786.00 ± 0 mg/g in monosodium glutamate. Calculated free glutamate intake from food by total respondents was 1.96 g/person/day; with intake by the Chinese was shown to be significantly (p=0.001) higher than Malays at 2.34 and 1.77 g/person/day, respectively. On the other hand, the average total free glutamate intake from condiments by total respondents was 0.27 g/person/day. The average total intake by the Malays, however, was significantly (p=0.004) higher than Chinese at 0.35 and 0.15 g/person/day, respectively. Overall, the average consumer need not be alarmed about the intake of glutamate from typical diet in their daily dietary pattern. Despite that, with heavy free glutamate intake (95th percentile) at more than 3.0 g/person/day may expose the consumers with possible adverse health effects.